SISTEM MONITORING PEMBERIAN MAKANAN TAMBAHAN BALITA BERBASIS WEB DI DESA KARANG REJO - Muhammad Al Fayed; Barany Fachri; Afif Badawi (CV. Hawari, 2026)
Toddlerhood is a critical period in a child’s growth and development that significantly affects future health and cognitive outcomes. Adequate nutritional intake during this stage is essential to prevent growth disorders, particularly stunting. The Indonesian government has implemented various intervention programs, including the Supplementary Feeding Program (Pemberian Makanan Tambahan/PMT), to improve toddlers’ nutritional status and reduce stunting, especially in areas with high nutritional challenges. In Karang Rejo Village, the PMT program is actively implemented through community health posts (posyandu). However, the management of PMT data, including beneficiary records, monitoring of weight and height, and feeding schedules, is still conducted manually. This manual approach leads to data inaccuracies, difficulties in tracking historical records, potential data loss, and delays in reporting. In addition, the lack of integrated data hinders health workers and cadres from conducting effective and regular monitoring, which may impact the accuracy of nutritional interventions for toddlers at risk of stunting. To address these issues, this study proposes the development of a web-based monitoring system for the PMT program. The system is designed to facilitate structured data recording, periodic monitoring of toddlers’ nutritional status, and real-time reporting accessible to authorized users. The implementation of this system is expected to improve the effectiveness and efficiency of PMT services, support timely decision-making, and contribute to government efforts in reducing stunting rates and improving the overall health status of toddlers in Karang Rejo Village.